Совершенствование методов расчета элементов машин с длительным сроком работы при действии многокомпонентной загрузки с учетом их утонения - Васильева, Т. А.; Теплицкий, Л. Л. (НТУ "ХПИ", 2013)
This paper describes a new approach to justification of parameters of machines elements designed for along term of work under the influence of multi-component loads taking into account their thinning during work. It's proposed to consider the combined effect of different types of loads to determine the resource of machines elements. It is suggested also to take into account the change of effective thickness, that takes place by the end of term of exploitation. Examples of the use of proposed approach to the analysis of frames of locomotives are presented.
Keywords: рама тепловоза; тепловоз магистральный; состояние напряженно-деформированное; коррозия